Motivations of inhabitants of large urban agglomerations to participate in mass running events - Malchrowicz-Mośko, Ewa; Poczta, Joanna; Młodzik, Maciej (Journal of Education, Health and Sport, 2017)
The article presents the results of empirical research on the motivation of inhabitants of large urban agglomerations to participate in mass running events such as marathons or half-marathons. The theoretical assumptions, the basis of the research and design of the standardized interview questionnaire were presented. Authors verified four groups of motifs by Freyer and Gross, and examined 232 runners – residents of large urban agglomerations, participants of the Poznań marathon to determine motives for participation in large running events. Most of the participants were residents of Poznań and its surroundings (185 persons), the rest (47 people) were residents of other big cities in Poland – active sport tourists. There were slight differences in the motifs of the participation of the inhabitants of the city in which the half-marathon is organized and tourists.